Comparison of efficiency and safety of rivaroxaban, apixaban and enoxaparin for thromboprophylaxis after arthroplastic surgery: a meta-analysis - Yu, Zhi (Biosci Rep, 2018)
Objective: To compare the efficacy and safety of rivaroxaban, apixaban and enoxaparin for thromboprophylaxis after arthroplastic surgery. Methods: We conducted a meta-analysis containing a wide range of randomized controlled trials about efficiency and safety of rivaroxaban, apixaban and enoxaparin for thromboprophylaxis after arthroplastic surgery in the recent decade from January 2006 to June 2018. The present study separately analyzed the following key components: the different efficiency and safety for rivaroxaban and enoxaparin; apixaban and enoxaparin; and enoxaparin and other new developed anticoagulants. Results: Sixteen studies containing 58885 patients were included. In results of efficacy outcomes, total events occurred in 4.89% patients of rivaroxaban group and 9.55% patients of the control group; however, no significant difference was observed in apixaban groups of their efficacy outcomes. Primary events didn’t show significant difference when comparing apixaban with the control or comparing enoxaparin with the control. In analysis of safety outcomes, bleeding events occurred in 3.41% patients of rivaroxaban group compared with 2.84% patients of the control groups; bleeding events in apixaban groups were 4.09% compared with the control groups 4.64%. Bleeding events occurred in 3.51% patients of enoxaparin group, slightly lower than 5.82% of the control group. Conclusion: Direct oral anticoagulant, rivaroxaban might have better efficacy outcomes in thromboprophylaxis after arthroplastic surgery; however, apixaban showed no significantly different efficacy outcomes compared with enoxaparin, and enoxaparin may have equal or even better safety outcomes compared with direct oral anticoagulants.